VD_FINDINFO Décision / 2013 / 704 vom 8. März 2013 - VD Tribunal cantonal (2013)
DÉTENTION PRÉVENTIVE, PROPORTIONNALITÉ, RISQUE DE RÉCIDIVE | 221 CPP (CH), 237 CPP (CH), 393 al. 1 let. c CPP (CH), 393 CPP (CH)